Performance Analysis On Idle Breeder Game - Wu, Steven; Agung Riyadi (LPPM & Fakultas Teknologi Informasi UNSAP, 2023)
The performance analysis is an essential process for evaluating the efficiency and effectiveness of a system or software. This study focused on conducting performance analysis of the mobile game